Menggagas Endowment Fund Bidang Hukum dan Keadilan: Upaya Mewujudkan Kesejahteraan dan Martabat Hakim - Adeng Septi Irawan (Judex Laguens, 2024)
Judges are the main figures in upholding law and justice in Indonesia, where their position is quite dominant in determining the legal fate of justice seekers. However, the position of judge does not guarantee good welfare. So far, it seems that the state is reluctant to provide optimization for the welfare of judges as stated in Government Regulation Number 94 of 2012 concerning Financial Rights and Facilities for Judges Under the Supreme Court. In addition, the Draft Law (RUU) on the Position of Judges seems to have never been discussed by the executive and legislative parties. This research plays a role in optimizing the welfare of judges. In this research, using a Library Research approach study (Kajian Pustaka) with a deductive analysis method (general to specific), the results of this research data show that it is clear that the independence and independence of the judiciary is greatly influenced by the executive and legislative institutions, thus affecting welfare. . judge. From this problem, the idea emerged to improve the welfare of judges in the form of a Law and Justice Endowment Fund sourced from the State Revenue and Expenditure Budget (APBN) or other legitimate sources. Please note, currently quite a lot of endowment funds have been distributed by the central government, including: endowment funds for education, research, higher education and culture as stated in Presidential Regulation Number 111 of 2021 concerning Endowment Funds in the Education Sector. Not to mention that in various regions regional endowment funds are starting to emerge in several fields. The aim of this endowment fund is to ensure the sustainability of certain fields that are important for future generations.